2020
DOI: 10.1055/s-0040-1708531
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Dynamic Mechanical Analysis in the Engineering of Amorphous Solid Dispersions

Abstract: AbstractDynamic mechanical analysis (DMA) offers several advantages over prevailing methods in the characterization of amorphous solid dispersions (ASDs) typically used for improving the delivery of poorly water-soluble drugs. This method of analysis, though underutilized in the study of pharmaceutical systems, is particularly attuned to rheological investigations of thermal and mechanical properties of solids such as ASDs. Its ability to determine the viscoelastic properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The Dynamic Mechanical Analyzer (DMA) is commonly used for this purpose. Small cycling loads are applied on the samples enabling determination of viscous and elastic components of the complex modulus and by simultaneous temperature variation an exact T g value can be obtained [ 68 , 85 ]. The technique can also be adapted with a chamber for relative humidity variation which enables assessment of humidity and its plasticizing effects.…”
Section: Product Development Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The Dynamic Mechanical Analyzer (DMA) is commonly used for this purpose. Small cycling loads are applied on the samples enabling determination of viscous and elastic components of the complex modulus and by simultaneous temperature variation an exact T g value can be obtained [ 68 , 85 ]. The technique can also be adapted with a chamber for relative humidity variation which enables assessment of humidity and its plasticizing effects.…”
Section: Product Development Strategymentioning
confidence: 99%
“…The technique can also be adapted with a chamber for relative humidity variation which enables assessment of humidity and its plasticizing effects. DMA is ideally suited for evaluation of HME extrudates [ 85 ], but also used for thin film ASD prepared by solvent evaporation. DMA can be used for identification of proper HME process parameters to obtain homogenous extrudates and to assess molecular mobility which can be linked to ASD physical stability [ 85 ].…”
Section: Product Development Strategymentioning
confidence: 99%
“…It has been found that DMA is able to detect amorphous phase domains as small as 10 nm, and thus, it is a useful technique to characterize solid dispersions . Moreover, in terms of controlling measurement conditions such as humidity, temperature, and frequency, DMA is more flexible than other conventional techniques, such as traditional rheology, to study ASDs . Earlier, using DMA to study the molecular relaxations in ASDs had some problems: (i) it is difficult to mount powder; (ii) it needs a special sample geometry; (iii) ASDs with high drug loadings are brittle and hence inappropriate for DMA analysis. , However, the DMA analyzer with a novel powder sample holder used in the present study helps us to completely eliminate these bottlenecks.…”
Section: Introductionmentioning
confidence: 99%